Influence of the interface strength on the mechanical properties of discontinuous tungsten fiber-reinforced tungsten composites produced by field assisted sintering technology. (April 2018) - Mao, Y.; Coenen, J.W.; Riesch, J.; Sistla, S.; Almanstötter, J.; Jasper, B.; Terra, A.; Höschen, T.; Gietl, H.; Linsmeier, Ch.; Broeckmann, C.
Abstract: In future fusion reactors, tungsten is a main candidate material for plasma-facing components. However, the intrinsic brittleness of tungsten is an issue under the extreme fusion environment. To overcome this drawback, tungsten fiber-reinforced tungsten (Wf /W) composites are being developed relying on an extrinsic toughening principle. In this study Wf /W composites are produced by a Field-Assisted Sintering Technology (FAST) process with different fiber–matrix interfaces. The fracture behavior was studied by 3-point bending tests on notched samples. 4-point bending tests and tensile tests are performed to measure the flexural strength and tensile strength, respectively. Wf /W with a weak interface shows a typical pseudo-ductile fracture behavior, similar to ceramic matrix composites. A strong interface is beneficial to achieve higher flexural strength and tensile strength, but in turn, weakens the pseudo-ductile behavior.